Then and now: changes in social organisation and livelihood of the Berawan community since the formation of Malaysia - Burkhardt, Jey Lingam; Burkhardt, Juergen Martin (UNIMAS Publisher, 2017)
The Berawan are a small Orang Ulu people group to which four longhouse communities belong: Long Jegan and Long Teru on the Tinjar River, and Long Terawan and Batu Belah on the Tutoh River.The Tutoh and the Tinjar aretributaries of the Baram river. This paper presents a socio-economic sketch of the Berawan in the early 1960s and contrasts it with the early 21st century situation. A picture is drawn of the social organisation and livelihood of the Berawan community. The following trends are discernible: Longhouse living has become more comfortable but at the same time more cash dependent. The education level of the Berawan has risen significantly while their opportunities to engage in traditional livelihood activities such as rice planting, hunting and fishing are reduced nowadays due to the conversion of vast tracts of lands into palm oil plantations and the silting of the rivers. This has increasingly led the younger generation to migrate out of the village. On the other hand, contrary to popular belief that the tourism industry has a primarily adverse influence on ethnic minority culture, we found that the economic value that tourism offers can promote local culture in encouraging people to remain on their ancestral land. Keywords: Berawan, Orang Ulu, social organisation, livelihood, indigenous peoples, Sarawak.